Relationship between strength, power, speed, and change of direction performance of female softball players - Nimphius, S.; McGuigan, M. R.; Newton, R. U. (The Journal of Strength and Conditioning Research, 2010)
The purpose of this study was to investigate (a) the cross-sectional relationship of strength, power, and performance variables in trained female athletes and (b) determine if the relationship between these variables changes over the course of a season. Ten female softball players (age = 18.1 +/- 1.6 years, height = 166.5 +/- 8.9 cm, and weight = 72.4 +/- 10.8 kg) from a state Australian Institute of Sport softball team were tested for maximal lower body strength (one repetition maximum [1RM]), peak force (PF), peak velocity (PV), and peak power (PP) during jump squats unloaded and loaded, unloaded countermovement vertical jump height (VJH) 1 base and 2 base sprint performance and change of direction performance on dominant and nondominant sides. The testing sessions occurred pre, mid, and post a 20-week training period. Relationship between body weight (BW), relative strength (1RM/BW), VJH, relative PP, relative PF, PV, speed, and change of direction variables were assessed by Pearson product-moment correlation coefficient at each testing session. Significant relationships were found across all time points with BW, speed, and change of direction measures (r = 0.70-0.93) and relative strength and measures of speed and change of direction ability (r = -0.73-0.85). There were no significant relationships between VJH and any measure of performance at any time point. In conclusion, BW and relative strength have strong to very strong correlations with speed and change of direction ability, and these correlations remain consistent over the course of the season. However, it seems as if many relationships vary with time, and their relationships should therefore be investigated longitudinally to better determine if these cross-sectional relationships truly reflect a deterministic relationship.